2020
DOI: 10.1038/s41559-020-1134-5
|View full text |Cite
|
Sign up to set email alerts
|

Community rescue in experimental phytoplankton communities facing severe herbicide pollution

Abstract: Evolutionary rescue occurs when adaptation prevents local extinction in deteriorating environments. Laboratory experiments with microorganisms have shown that the likelihood of evolutionary rescue is greatest in large populations that have previously experienced sublethal doses of stress. To assess this result in natural communities, we conducted a mesocosm experiment with semi-natural phytoplankton communities exposed to glyphosate, a widely used herbicide. We tested whether community biomass and pre-exposure… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
62
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 86 publications
(90 reference statements)
11
62
1
Order By: Relevance
“…Other studies have reported increases in phytoplankton in the presence of glyphosate, attributing this fertilising effect to glyphosate-derived P (Forlani et al, 2008;Harris & Smith, 2016;Pérez et al, 2007;Saxton et al, 2011). The parallel study by Fugère et al (2020) showed that glyphosate led to dosedependent increases in TP and chl-a concentrations in our ponds, presumably as a result of phytoplankton P-limitation (initial N:P ratio ~33). Taken in context with our results, it appears that glyphosate-mediated increases in algal resources enhanced the growth of tolerant cladocerans.…”
Section: Community Responses To Agrochemicalssupporting
confidence: 61%
“…Other studies have reported increases in phytoplankton in the presence of glyphosate, attributing this fertilising effect to glyphosate-derived P (Forlani et al, 2008;Harris & Smith, 2016;Pérez et al, 2007;Saxton et al, 2011). The parallel study by Fugère et al (2020) showed that glyphosate led to dosedependent increases in TP and chl-a concentrations in our ponds, presumably as a result of phytoplankton P-limitation (initial N:P ratio ~33). Taken in context with our results, it appears that glyphosate-mediated increases in algal resources enhanced the growth of tolerant cladocerans.…”
Section: Community Responses To Agrochemicalssupporting
confidence: 61%
“…A few recent studies have expanded the scope of evolutionary rescue from populations to diverse assemblages of species and examined evolutionary rescue in entire communities confronted with severe stress (Fussmann and Gonzalez, 2013;Low-Décarie et al, 2015;Bell et al, 2019;Fugère et al, 2020). Community rescue occurs when the populations of multiple species recover rapidly following exposure to levels of stress that were lethal to the community in its ancestral form, allowing a community to recover both abundance and diversity in severely degraded environments (Low-Décarie et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Community rescue occurs when the populations of multiple species recover rapidly following exposure to levels of stress that were lethal to the community in its ancestral form, allowing a community to recover both abundance and diversity in severely degraded environments (Low-Décarie et al, 2015). Some key factors promoting evolutionary rescue of populations were also found to favor community rescue (Low-Décarie et al, 2015;Bell et al, 2019;Fugère et al, 2020). First, a history of stress exposure increases the relative frequency of stress-resistant individuals in communities, which provides a correlated advantage at a higher dose of stress and thus facilitates rescue.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, species may have rapidly adapted through phenotypic plasticity (Chevin et al 2013) or evolution, either via selection on standing genetic variation (Barrett and Schluter 2008) or de novo mutations. Thus, preselection to stress may allow a degree of community tolerance, through a combination of ecological sorting and evolutionary selection which can also maintain ecosystem function (Bell et al 2019, Fugère et al 2020. Phytoplankton typically double population sizes within one to a few days, depending on the environmental conditions (Reynolds 1984).…”
Section: Discussionmentioning
confidence: 99%
“…However, at doses initially lethal for all species only rapid evolution can allow the recovery of an exposed community (unless the system is open to immigration of resistant genotypes). Previous work has shown that exposure to nonlethal stress can pre-adapt populations to a subsequent exposure to otherwise lethal press perturbation allowing resident species and genotypes to adjust their physiology and demographic rates (Bell and Gonzalez 2009, 2011, Low-Décarie et al 2015, Fugère et al 2020). Exposure to a stressor may thus reduce the effects of subsequent exposure to the same stressor (Bell and Gonzalez 2009, 2011, Low-Décarie et al 2015, Fugère et al 2020) due to selection for tolerant/resistant genotypes within the populations comprising the community.…”
Section: Introductionmentioning
confidence: 99%